Wasted lives and expulsions. A study of Beasts of the Southern Wild by Benh Zeitlin - Gajewska, Grażyna (Images. The International Journal of European Film, Performing Arts and Audiovisual Communication, 2023)
The author analyzes the mutual determinants of the ecological and social crisis. The starting point is Zygmunt Bauman’s concept of wasted lives and the concept of expulsions proposed by Saskia Sassen, referring both to activities destroying specific areas and the communities inhabiting them. This frame includes films showing various scenarios of a dystopian future in which individual characters or entire groups have been consumed and expelled by the aggressive Capithalocene and doomed to live in the dustbin of contemporary civilization. The article focuses on the production Beasts of the Southern Wild directed by Benh Zeitlin. The author looks at the reality and, at the same time, the symbolism of the film’s wall/dam; communities living on both sides of it, relationships between nature and culture, or rather (in posthumanist terms it is written as one word – natureculture); the methods and consequences of excluding and expelling human and non-human beings used by the mechanisms of late capitalism.